2007
DOI: 10.1152/ajpcell.00447.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of anion exchanger Slc26a6 by protein kinase C

Abstract: (CFEX, PAT1) is an anion exchanger expressed in several tissues including renal proximal tubule, pancreatic duct, small intestine, liver, stomach, and heart. It has recently been reported that PKC activation inhibits A6-mediated Cl/HCO 3 exchange by disrupting binding of carbonic anhydrase to A6. However, A6 can operate in HCO 3-independent exchange modes of physiological importance, as A6-mediated Cl/ oxalate exchange plays important roles in proximal tubule NaCl reabsorption and intestinal oxalate secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 41 publications
7
55
1
Order By: Relevance
“…Another possibility is that the PKC activators cause membrane retrieval of the channel, therefore decreasing its functional expression. This has been reported for other membrane proteins expressed in oocytes like ␣␤␥-rENaC (1), type II Na ϩ -P i cotransporters (16), glutamate transporter EAAC1 (35), and anion exchanger SLC26A6 (22). The effects of PMA on membrane retrieval could be specific to the membrane protein expressed in oocytes or general endocytosis of the plasma membrane (1).…”
Section: Discussionmentioning
confidence: 54%
“…Another possibility is that the PKC activators cause membrane retrieval of the channel, therefore decreasing its functional expression. This has been reported for other membrane proteins expressed in oocytes like ␣␤␥-rENaC (1), type II Na ϩ -P i cotransporters (16), glutamate transporter EAAC1 (35), and anion exchanger SLC26A6 (22). The effects of PMA on membrane retrieval could be specific to the membrane protein expressed in oocytes or general endocytosis of the plasma membrane (1).…”
Section: Discussionmentioning
confidence: 54%
“…This is a novel finding because our previous pharmacological studies revealed that PMA-induced internalization of NKCC1 is dependent upon isoform PKC⑀ (12). In other studies, nPKC and cPKCs have been suggested to regulate membrane protein surface expression, but in all these instances the identity of the specific PKC isoform is only inferable through the use of pharmacological inhibitors (19,60,61). Knockdown of the PKC isoforms did not change steadystate TER (Table 1), suggesting it does not affect the constitutive maintenance of tight junction integrity under these conditions.…”
mentioning
confidence: 78%
“…The STAS domains of human SLC26A3 (29) and human SLC26A9 (53) interact in vitro with the phosphorylated R domain of CFTR, but the reported regulatory interactions of SLC26 polypeptides and CFTR in vitro and in vivo have varied. PKC phosphorylation of the human SLC26A6 STAS domain has been suggested to regulate Cl Ϫ /HCO 3 Ϫ exchange activity through CAII binding (54), but this phosphorylation did not regulate oxalate transport (55), and its relationship to CFTR is unknown. Although the R domain of CFTR is not shared among other ABC proteins, Rv1739c might function as a regulator of the M. tuberculosis ABC family sulfate permease CysTWA (15).…”
mentioning
confidence: 99%